Effect of foliar application of salicylic acid and mycorrhiza on quantitative and qualitative traits of maize - M. P. Younespour; M. Samdeliri; P. Mazloom; A. M. Mirkalaei; M. Moballeghi (Brazilian Journal of Biology, 2023)
Abstract An experiment was performed to investigate the effect of mycorrhizal symbiosis and foliar application of salicylic acid on quantitative and qualitative traits of maize during 2018 and 2019 in the research farm of Islamic Azad University, Chalous Branch. Split plot in a randomized complete block design with three replications was used. Experimental factors included mycorrhiza species of (G. mosseae), (G. geosporum) and (G. intraradices) at two levels (no consumption and consumption of mycorrhiza) and salicylic acid at two levels (no consumption and consumption of 1 mμ of salicylic acid). Results of interaction effects of mycorrhiza and salicylic acid on the measured traits revealed that the maximum 1000-grain weight, grain yield, biological yield, phosphorus, potassium, nitrogen percentage and yield of maize grain protein were observed in G. mosseae treatment under foliar application of salicylic acid. Foliar application of salicylic acid increases the root length and provides the necessary conditions for increasing water and nutrient uptake alongwith increase in photosynthesis and thus allocates more photosynthetic substance for development of reproductive organs. Hence, it increases maize grain weight and accordingly grain yield. In general, the results revealed that mycorrhiza and foliar application of salicylic acid increase growth indicators, yield and yield components. It also improved the quality traits of the maize plant. Based on results, the interaction effect of G. mosseae treatment and foliar application of salicylic acid yielded better results than other treatments. Mycorrhiza increases the number of grain in the ear, the number of rows in the ear, increases the plant's ability to absorb phosphorus, and the increase of mycorrhiza along with salicylic acid shows the maximum grain yield in maize. Finally, it can be concluded that the use of mycorrhiza and salicylic acid can be effective in increasing grain in the plant.